Influence Of Amprolinsile And Brovitacoccid On The Protein Synthesizing Function Of The Liver And Enzyme Activity In Turkey Blood Serum During Eimeria Invasion - Gutyj, B.; Stybel, V.; Hariv, I.; Maksymovych, I.; Buczek, K.; Staniec, M.; Milczak, A.; Bushueva, I. V.; Kulish, S. M.; Shcherbyna, R. O.; Samura, T. O.; Бушуєва, Інна Володимирівна; et al. (My University, 2019)
While parasitizing in the intestinal mucosa, Eimeria releases metabolic products, which have a toxic influence on the various systems and tissues of turkeys. When Brovitacoccid is used for treatment, owing to its antiprotozoal action, it eliminates the action of toxins on the liver and intestinal mucosa. However, the recovery of the protein synthesizing function of the liver occurs 10 days after clinical recovery, but when using Amprolinsile, the restoration of the protein synthesizing function of the liver begins on the 5th day of treatment. During the research on the therapeutic effectiveness of Amprolinsile, in comparison with Brovitacoccid, for spontaneous Eimeria invasion, it was noticed that when using Amprolinsile for treatment, general aminotransferase activity was slightly higher than the normal range, on the 5th day. However, the coefficient of AST/ALT levels was within the normal physiological value range. This indicates that there is a stabilization of permeability of the outer cell membranes of hepatocytes as well as the internal mitochondrial membranes. It was determined that using Amprolinsile to treat turkeys, compared to Brovitacoccid, results in a faster normalization of the protein synthesizing function of the liver, and enzyme activity in blood serum as well.
Keywords: pharmacology; Brovitacoccid; Amprolinsile; protein–synthesizing function of the liver; blood serum enzymes; turkeys; Eimeria